Stress syndromes of the elbow joint region (golfer’s/tennis elbow) - a review of the recent literature - Zwolski, Maciej; Puchalski, Krzysztof; Klocek, Konrad; Hajduk, Aleksandra; Mrozek, Łukasz; Kostecki, Bartosz; Szumlas, Zuzanna; Jurek, Aleksander; Tekielak, Anna (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Tennis elbow and golfer’s elbow are two stress syndromes of the elbow joint region which have received much attention due to their effects on everyday and sporting activities. This review intends to provide an up-to-date summary of the pathophysiology, clinical manifestation, diagnostic techniques, and treatment options for the two conditions. State of Knowledge: Recent research has emphasized the complexity of these diseases, connecting various causes to their emergence. The current study also shows how inflammation, tendon degradation, and neural involvement contribute to these disorders. Imaging advancements, such as ultrasound and MRI, have improved the diagnostic process by allowing visualization and recognition of underlying disorders. To ensure proper management, differential diagnoses, such as nerve compression syndromes and other musculoskeletal diseases, must be carefully evaluated. Rest, physiotherapy, NSAIDs, and corticosteroid injections are important first-line treatments. Novel therapeutic interventions, such as PRP therapy and ESWT have recently been studied as supplements or alternatives to traditional procedures. The exercise-based rehabilitation in controlling and preventing recurrence is also emphasized. Although surgery is reserved for the most difficult cases, advances in minimally invasive techniques have resulted in better outcomes. Conclusion: Recent literature has significantly contributed to our understanding of elbow stress syndromes. The synthesis of recent research provides clinicians with valuable insights into optimal management strategies. Although, further research is crucial to improve diagnosis, develop new treatments, and raise the standard of care for those affected by these conditions.